Chemical Biology Screen for Prostate Cancer Therapeutics - Ketola, Kirsi (fi=Turun yliopisto|en=University of Turku|, 2011)
Prostate cancer initially responds to hormone-based therapeutics such as anti-androgen treatment or chemotherapeutics but eventually becomes resistant. Novel treatment options are therefore urgently needed. This thesis study applied a high-throughput screen of 4910 known drugs and drug-like small molecules to identify compounds that selectively inhibit growth of prostate cancer cells. In addition, the mechanisms underlying the cellular sensitivity to potent cancer selective compounds were addressed. Surprisingly, many of the compounds currently used in the clinics or studied in clinical trials were not cancer-selective. Only four drugs, aldehyde dehydrogenase inhibitor disulfiram (Antabus), antibiotic ionophore monensin, histone deacetylase inhibitor tricostatin A and fungicide thiram inhibited prostate cancer cell growth at nanomolar concentrations without major effects on non-malignant prostate epithelial cells. Disulfiram, monensin and a structurally similar compound to monensin, salinomycin, induced oxidative stress and inhibited aldehyde dehydrogenase activity. Moreover, monensin and salinomycin reduced androgen receptor signalling and steroidogenesis, enforced cell differentiation and reduced the overall levels of cancer stem cells. Taken together, novel and potentially prostate cancer-selective therapeutic agents were identified in this study, including the description of a multitude of intoxicating mechanisms such as those relating to oxidative stress. The results provide novel insights into prostate cancer biology and exemplify useful means of considering novel approaches to cancer treatment.